2022
DOI: 10.1111/cea.14106
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of atopic diseases and gastro‐oesophageal reflux: evidence of a shared cause

Abstract: Introduction: Gastro-oesophageal reflux disease (GERD) is the most common nonallergic comorbidity in adults with asthma; however, comorbidity with other atopic diseases such as eczema and hay fever is unclear. The objective was to assess the comorbidity of GERD with asthma and atopic diseases and to investigate possible mechanisms, including genetic and/or affective factors. Methods:A co-twin control study harnessing 46 583 adult twins. Questionnaires on health status were linked to national patient and prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…In a Swedish twin study, the risk of GERD in study participants with asthma was OR 1.52 but additional analyses found no differences in comorbidity estimates for asthma diagnosed in childhood or adulthood 32. In our study, risk of having GERD was OR 2.05 among people with asthma compared with non-asthmatics.…”
Section: Discussioncontrasting
confidence: 64%
“…In a Swedish twin study, the risk of GERD in study participants with asthma was OR 1.52 but additional analyses found no differences in comorbidity estimates for asthma diagnosed in childhood or adulthood 32. In our study, risk of having GERD was OR 2.05 among people with asthma compared with non-asthmatics.…”
Section: Discussioncontrasting
confidence: 64%
“…Conversely, Brew et al concluded that patients with AD are at risk of having GERD. In their large twin cohort, the odds of having GERD comorbidity in patients with AD were found to be OR 1.23 (95%CI 1.10-1.38) [82].…”
Section: Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 99%
“…Furthermore, they proposed that a shared component involving affective traits, such as neuroticism, depression, or anxiety, may play a role. They implied that having an atopic disease may increase the risk of depression, anxiety, or neuroticism, which in turn triggers GERD [82]. Undoubtedly, further research is needed to establish the relationship between AD and GERD.…”
Section: Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 99%
“…However, it was suggested that a shared component, including emotional disorders, rather than a causal relationships may be significant. 45 Therefore, 2 possible mechanisms of action have been proposed: mediation, in which having an atopic disease increases the risk of depression, anxiety, or neuroticism which then trigger and exacerbate GERD; or a common cause, in which having depression, anxiety, or neuroticism increases vulnerability to developing or reporting both atopic diseases and GERD.…”
mentioning
confidence: 99%